2003
DOI: 10.1242/jeb.00334
|View full text |Cite
|
Sign up to set email alerts
|

A new intracellular pathway of haem detoxification in the midgut of the cattle tick Boophilus microplus: aggregation inside a specialized organelle, the hemosome

Abstract: The hard tick Boophilus microplus ingests large volumes of cattle blood, as much as 100 times its own mass before feeding. Huge amounts of haem are produced during haemoglobin digestion, which takes place inside acidic lysosomal-type vacuoles of the digest cells of the midgut. Haem is a promoter of free radical formation, so haemoglobin digestion poses an intense oxidative challenge to this animal.In the present study we followed the fate of the haem derived from haemoglobin hydrolysis in the digest cells of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 27 publications
(24 reference statements)
9
86
0
4
Order By: Relevance
“…At 2·h (Fig.·5A), Pd-mP was visible as a yellow-green fluorescence, associated mainly with the large vesicles of digest cells (the vesicles implicated in hemoglobin uptake in Fig.·1A), but some fluorescence was also found in the cytosol, in contrast to hemosomes, which were almost devoid of label at this time (Fig.·5A). At 6·h (Fig.·5B), the Pd-mP fluorescence had reached the hemosomes, showing that the Pd-mP generated from digestion of Pd-mP-globin in vivo followed the same path suggested previously for heme accumulation in the digest cell (Lara et al, 2003).…”
Section: Pd-mp-globin Uptake By Digest Cells In Vivosupporting
confidence: 74%
See 1 more Smart Citation
“…At 2·h (Fig.·5A), Pd-mP was visible as a yellow-green fluorescence, associated mainly with the large vesicles of digest cells (the vesicles implicated in hemoglobin uptake in Fig.·1A), but some fluorescence was also found in the cytosol, in contrast to hemosomes, which were almost devoid of label at this time (Fig.·5A). At 6·h (Fig.·5B), the Pd-mP fluorescence had reached the hemosomes, showing that the Pd-mP generated from digestion of Pd-mP-globin in vivo followed the same path suggested previously for heme accumulation in the digest cell (Lara et al, 2003).…”
Section: Pd-mp-globin Uptake By Digest Cells In Vivosupporting
confidence: 74%
“…Hemoglobin is thought to be hydrolyzed in the digestive vacuoles of these cells (Agbede et al, 1985;Walker and Fletcher, 1987) by the action of acid proteases (Mendiola et al, 1997), therefore releasing huge amounts of heme inside these cells. We have recently shown that most of the heme produced by this process is ultimately accumulated inside a specialized organelle called a hemosome, forming a unique type of heme aggregate (Lara et al, 2003). Using globin reconstituted with Pd-mP, a fluorescent metalloporphyrin employed here as a heme analog, we studied hemoglobin degradation in living digest cells of the cattle tick Boophilus microplus.…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not this is unique to I. scapularis or that iron-binding proteins were injected at below detectable levels needs further investigation. Published evidence has suggested that the tick may detoxify heme/iron through sequestration in digestive cells (hemosomes) [118,119] and hemolymph [120][121][122]. Data in this study and others [40,41,50,52,123] that show secretion of heme binding proteins in tick saliva suggest a third possibility of eliminating heme through tick saliva.…”
Section: Heme-binding Proteinssupporting
confidence: 51%
“…Iron from the blood meal may be in the form of heme or host-transferrinbound iron. Excessive heme resulting from hemoglobin degradation aggregates in specialized organelles called hemosomes within the digestive cells of the midgut as a detoxification mechanism (Lara et al, 2003). In the hard tick H. longicornis, intracellular ferritin has been previously identified, but its function has not been described (Xu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%